Edge-Based IoT EndPoint Performance Optimization for Smart Mosques - Rosad, Safiq; lasimin, lasimin; Irkhamudin, Faik; Pramudita, Cahyaning Yuniar; Alifah, Shofari Rizqi (Institut Teknologi Dirgantara Adisutjipto, 2025)
This study examines the performance optimization of IoT endpoints based on edge architecture in a Smart Mosque system to improve the efficiency of managing electronic devices such as room lighting, air conditioning, and loudspeakers according to prayer schedules. The main problems faced include limited internet connectivity and the need for real-time service availability with minimal latency. The research objective is to test and implement optimization techniques such as data caching on the edge, decoupled computation, and push mechanisms using Server-Sent Events (SSE) and WebSocket to reduce latency and strengthen service availability. The methods used include prototype design with ESP32 endpoints, testing p50, p95, and p99 percentile latencies, and monitoring service availability and network resilience in baseline and optimized push mode scenarios. The test results show a significant reduction in average and tail latency, an increase in service availability approaching 99%, and system continuity during network disruptions. These findings confirm that edge computing architecture is very effective in supporting time-critical IoT systems such as Smart Mosques.